Genetic Parameters and Inbreeding Effect of Morphological Traits in Sardinian Anglo Arab Horse - Andrea Giontella; Francesca Maria Sarti; Giovanni Paolo Biggio; Samira Giovannini; Raffaele Cherchi; Camillo Pieramati; Maurizio Silvestrelli (Animals, 2020)
The purpose of this study was to estimate the heritability and genetic correlations of four biometric measurements and an overall score (OS) in the Sardinian Anglo-Arab horse (SAA); moreover, the effect of inbreeding on these traits was investigated. A dataset with 43,624 horses (27,052 females and 16,572 males) was provided by the Agricultural Research Agency of Sardinia (AGRIS). Cannon bone circumference (BC), chest girth (CG), shoulder length (SL), and withers height (WH) were measured on 6033 SAA horses born in Sardinia between 1967 and 2005; beside the measurements, an overall score (OS) was taken comparing the morphology of each horse to an “ideal type” that is scored out of 100. The mean value is 20.5 cm for BC, 185.9 cm for CG, 67.6 cm for SL, 160.8 cm for WH, and 73.2 for the OS. The heritability estimates ranged from 0.78 to 0.23. The results allow to foresee high genetic progress through the breeding programs. The most affected trait by the inbreeding rate seems to only be the withers height.